Propuesta para la Elaboración de la Matriz de Riesgo como Herramienta para una Auditoría Eficiente (2022)
The purpose of this article is to suggest the design of an audit risk matrix as a tool for the auditor, accountant and/or students that allows them to prioritize efforts in risk management in a more effective and efficient way, in the The proposal considers the variables or components of the inherent audit, control and detection risks, the risk assessment process, which corresponds to the identification, analysis, evaluation and treatment of the same; based on the risks identified in the items of the financial statements during the basic audit process in the planning and execution phases that have a direct impact on risk management, without neglecting the responsibility of the auditor in relation to the assignment , as well as the importance of implementing controls that can detect, prevent and mitigate the risks of fraud and/or significant errors that may exist in the financial statements and affect the decisions and objectives of the company.